One Step Toward More Research on Aging Masculinities: Operationalizing the Hegemonic Masculinity for Older Men Scale (HMOMS). Issue 2 (June 2019) - Springer, Kristen W.; Mouzon, Dawne M.
Extensive research has documented how hegemonic conceptions of masculinity shape men's behaviors, beliefs, and health. However, most research focuses on younger men and most datasets of aging adults do not include measures of masculinity. This two-pronged omission renders older men relatively invisible. Part of the reason for this invisibility is the lack of reliable, validated measures of masculinity applicable to aging men. In this project, we document, describe, and validate an eight-item hegemonic masculinity measure administered to more than 1, 000 older men ( 65 years old). Multivariate analyses predicting gender-typed hobbies consistently validate this Hegemonic Masculinity for Older Men Scale (HMOMS), pointing to the HMOMS as an exciting new option for further exploring the nuances and correlates of masculinity ideals among aging men.